-7(-2x+5)=-203

Simple and best practice solution for -7(-2x+5)=-203 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(-2x+5)=-203 equation:


Simplifying
-7(-2x + 5) = -203

Reorder the terms:
-7(5 + -2x) = -203
(5 * -7 + -2x * -7) = -203
(-35 + 14x) = -203

Solving
-35 + 14x = -203

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '35' to each side of the equation.
-35 + 35 + 14x = -203 + 35

Combine like terms: -35 + 35 = 0
0 + 14x = -203 + 35
14x = -203 + 35

Combine like terms: -203 + 35 = -168
14x = -168

Divide each side by '14'.
x = -12

Simplifying
x = -12

See similar equations:

| -3/110+2 | | 3/5*-1/22 | | 5x+10=82-4 | | 0.35-2.95=0.5(x-5) | | (3)/4(x-1)=x-3 | | 12x+50= | | 5(V+2)-8V=25 | | -3*-15/2 | | (9-8)8= | | f(x)=260 | | 3v+19=5v-5 | | 1(p)=8 | | 6x+41=-37 | | 12x^3+16x^2-5x-3=0 | | -5/2*3 | | -9x-45=18 | | c+13=6c+8 | | -3x+6=20 | | -4/3*3 | | 0.15-3.25=0.4(x-5) | | -5/22+11/5 | | -5x+15=-55 | | j-2(1-2j)=(39j-3)+5 | | 3x+x^2=-x+3 | | -2=-2y | | 5*-1/22 | | 3x+x^2=-1x+3 | | -21+5x=-76 | | -(4y+1)-(-3y-4)=-3 | | 3x^2=1350 | | 4x-6-3x=-2 | | -45+6x=51 |

Equations solver categories